Oxymatrine Inhibits Influenza A Virus Replication and Inflammation via TLR4, p38 MAPK and NF-κB Pathways - Dai, Jian-Ping (Int J Mol Sci, 2018)
Oxymatrine (OMT) is a strong immunosuppressive agent that has been used in the clinic for many years. In the present study, by using plaque inhibition, luciferase reporter plasmids, qRT-PCR, western blotting, and ELISA assays, we have investigated the effect and mechanism of OMT on influenza A virus (IAV) replication and IAV-induced inflammation in vitro and in vivo. The results showed that OMT had excellent anti-IAV activity on eight IAV strains in vitro. OMT could significantly decrease the promoter activity of TLR3, TLR4, TLR7, MyD88, and TRAF6 genes, inhibit IAV-induced activations of Akt, ERK1/2, p38 MAPK, and NF-κB pathways, and suppress the expressions of inflammatory cytokines and MMP-2/-9. Activators of TLR4, p38 MAPK and NF-κB pathways could significantly antagonize the anti-IAV activity of OMT in vitro, including IAV replication and IAV-induced cytopathogenic effect (CPE). Furthermore, OMT could reduce the loss of body weight, significantly increase the survival rate of IAV-infected mice, decrease the lung index, pulmonary inflammation and lung viral titter, and improve pulmonary histopathological changes. In conclusion, OMT possesses anti-IAV and anti-inflammatory activities, the mechanism of action may be linked to its ability to inhibit IAV-induced activations of TLR4, p38 MAPK, and NF-κB pathways.